2014
DOI: 10.1007/s00774-014-0619-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and bone metabolic indices in male master rowers

Abstract: The purpose of this study was to assess bone mass and bone metabolic indices in master athletes who regularly perform rowing exercises. The study was performed in 29 men: 14 master rowers and 15 non-athletic, body mass index-matched controls. Dual-energy X-ray absorptiometry measurements of the areal bone mineral density (aBMD) were performed for the total body, regional areas (arms, total forearms, trunk, thoracic spine, pelvis, and legs), lumbar spine (L1-L4), left hip (total hip and femoral neck), and forea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A single study was identified for each of BMI in MA rowers [ 57 ], MA rugby union [ 58 ] and MA x-country skiers [ 59 ]. Sliwicka and colleagues [ 57 ] found a non-significant (p = 0.482) difference between master rowers and active-professional controls; the rowers had a +2.3% higher mean BMI as compared to the control group (25.4 vs 24.8 kg/m 2 ). Climstein and colleagues [ 58 ] investigated master rugby union athletes who participated in the International Golden Oldies World Rugby festival.…”
Section: Resultsmentioning
confidence: 99%
“…A single study was identified for each of BMI in MA rowers [ 57 ], MA rugby union [ 58 ] and MA x-country skiers [ 59 ]. Sliwicka and colleagues [ 57 ] found a non-significant (p = 0.482) difference between master rowers and active-professional controls; the rowers had a +2.3% higher mean BMI as compared to the control group (25.4 vs 24.8 kg/m 2 ). Climstein and colleagues [ 58 ] investigated master rugby union athletes who participated in the International Golden Oldies World Rugby festival.…”
Section: Resultsmentioning
confidence: 99%
“…Regular rowing provides a number of health benefits to the masters athlete ( 8 ), such as improving serum cholesterol levels ( 20 ) and preventing sarcopenia ( 21 ) and bone weakening ( 22 ). As a non-high-impact sport ( 10 ), rowing is suitable for people who underwent total hip ( 23 , 24 ) or knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma visfatin did not differ between less than moderately trained subjects and experienced ultramarathon runners but, in this latter group it was two-fold induced after a mountain ultramarathon (39). Similarly, despite the worse metabolic profile, sedentary subjects had comparable serum visfatin concentration than professional rowers (238). Patients with metabolic syndrome had higher plasma visfatin than their age-matched counterparts which was correlated with lumbar spine BMD in men (239).…”
Section: Immuno-mediated Effects Of Exercise and Training On Bonementioning
confidence: 99%